EKSPLORASI SOAL MATEMATIKA PADA KONFLIK SKENARIO PROGRAM CERITA GAUSSEULIER EPISODE “THE TRUE HERO” - Dwianto Humardhani (Saraswati)
Today the children's interest towards animation is very high, both in the form of games and film animation story. It is inversely proportional to the child's interest in learning, especially subjects that are generally not favored by the majority of children, math. This would be very good if the animation used as a media of learning for children. The purpose of this paper is to presents the story in the forms of animation programs which contains the elements of mathematics education, providing learning of mathematics in the form of word problems, as well as broadens the variety of creations of television programs in the Faculty of Arts of Media Recording majoring Television. The artwork is a serial story program for children age 7-12 years at presentation packed into the form of an animation program. The concept of aesthetic creation of this artwork in the form of exploration of mathematical problems will be presented, the exploration refers to the manufacture of math problems are packed into a story program. The conclusion of this work is the making of mathematics that is identical to the complicated problems can be made fun if presented in the proper way, this is what is expected to stimulate children's interest in learning and improving the quality of a child's thinking.   Keywords: scenario, animation, math problems